Pragmatic Analysis of Ambiguity as Part of Forensic Linguistic Examination of Texts on Cases Related to Countering Extremism - O. V. Kozhara (Теория и практика судебной экспертизы, 2023)
The article discusses the theoretical and methodological grounds for establishing the “intentional” nature of ambiguity when conducting a linguistic analysis on cases related to countering extremism. The author addresses the concept of “intentional” ambiguity from the point of view of pragmatic functions implemented by ambiguity in different types of discourse. In particular, the paper shows that ambiguity in the “extremist” discourse performs not only the rhetorical function of influencing the addressee, but also contributes to the implementation of the author’s communicative strategies such as leveling the negative (“extremist”) meaning, absolving the author of responsibility. This justifies the need for a pragmatic analysis of ambiguity. Establishing of “intentional” ambiguity in the texts as part of forensic linguistic analysis involves a comprehensive study of the text’s genre specifics, as well as the author’s intentions and the recipient’s expectations implied. Accounting for these characteristics ensures the validity of the expert’s conclusions about the “intentional” nature of ambiguity, as well as the probability of “extremist” meaning in the analyzed context.